The toll-like receptor family protein RP105/MD1 complex is involved in the immunoregulatory effect of exopolysaccharides from Lactobacillus plantarum N14 - Murofushi, Yo (2015)
The radioprotective 105 (RP105)/MD1 complex is a member of the Toll-like receptor (TLR) family. It was reported that RP105/MD1 cooperates with the lipopolysaccharide (LPS) receptor TLR4/MD2 complex and plays a crucial role in the response of immune cells to LPS. This work evaluated whether RP105, TLR4 or TLR2 were involved in the immunoregulatory capacities of Lactobacillus plantarum N14 (LP14) or its exopolysaccharides (EPS). EPS from LP14 were fractionated into neutral (NPS) and acidic (APS) EPS by anion exchange chromatography. Experiments with transfectant HEKRP105/MD1 and HEKTLR2 cells demonstrated that LP14 strongly activated NF-κB via RP105 and TLR2. When we studied the capacity of APS to activate NF-κB pathway in HEKRP105/MD1 and HEKTLR4 cells; we observed that APS strongly stimulated both transfectant cells. Our results also showed that LP14 and APS were able to decrease the production of pro-inflammatory cytokines (IL-6, IL-8 and MCP-1) in porcine intestinal epithelial (PIE) cells in response to enterotoxigenic Escherichia coli (ETEC) challenge. In order to confirm the role of TLR2, TLR4 and RP105 in the immunoregulatory effect of APS from LP14, we used small interfering RNA (siRNA) to knockdown these receptors in PIE cells. The capacity of LP14 and APS to modulate pro-inflammatory cytokine expression was significantly reduced in PIERP105-/- cells. It was also shown that LP14 and APS were capable of upregulating negative regulators of the TLR signaling in PIE cells. This work describes for the first time that a Lactobacillus strain and its EPS reduce inflammation in intestinal epithelial cells in a RP105/MD1-dependend manner.